A New Autosomal Myh11-CreERT2 Smooth Muscle Cell Lineage Tracing and Gene Knockout Mouse Model—Brief Report. Issue 2 (15th December 2022) - Deaton, Rebecca A.; Bulut, Gamze; Serbulea, Vlad; Salamon, Anita; Shankman, Laura S.; Nguyen, Anh Tram; Owens, Gary K.
Abstract : Background: The Myh11 promoter is extensively used as a smooth muscle cell (SMC) Cre-driver and is regarded as the most restrictive and specific promoter available to study SMCs. Unfortunately, in the existing Myh11-CreER T2 mouse, the transgene was inserted on the Y chromosome precluding the study of female mice. Given the importance of including sex as a biological variable and that numerous SMC-based diseases have a sex-dependent bias, the field has been tremendously limited by the lack of a model to study both sexes. Here, we describe a new autosomal Myh11-CreER T2 mouse (referred to as Myh11-CreER T2 -RAD ), which allows for SMC-specific lineage tracing and gene knockout studies in vivo using both male and female mice. Methods: A Myh11-CreER T2 -RAD transgenic C57BL/6 mouse line was generated using bacterial artificial chromosome clone RP23-151J22 modified to contain a Cre-ER T2 after the Myh11 start codon. Myh11-CreER T2 -RAD mice were crossed with 2 different fluorescent reporter mice and tested for SMC-specific labeling by flow cytometric and immunofluorescence analyses. Results: Myh11-CreER T2 -RAD transgene insertion was determined to be on mouse chromosome 2. Myh11-CreER T2 -RAD fluorescent reporter mice showed Cre-dependent, tamoxifen-inducible labeling of SMCs equivalent to the widely used Myh11-CreER T2 mice. Labeling was equivalent in both male and female Cre + mice and was limited to vascular and visceral SMCs and pericytes in various tissues as assessed by immunofluorescence. Conclusions: We generated and validated the function of an autosomal Myh11-CreER T2 -RAD mouse that can be used to assess sex as a biological variable with respect to the normal and pathophysiological functions of SMCs.